Photography by Cameras Integrated in Smartphones as a Tool for Analytical Chemistry Represented by an Butyrylcholinesterase Activity Assay - Pohanka, Miroslav (Sensors (Basel, Switzerland), 2015)
Smartphones are popular devices frequently equipped with sensitive sensors and great computational ability. Despite the widespread availability of smartphones, practical uses in analytical chemistry are limited, though some papers have proposed promising applications. In the present paper, a smartphone is used as a tool for the determination of cholinesterasemia i.e., the determination of a biochemical marker butyrylcholinesterase (BChE). The work should demonstrate suitability of a smartphone-integrated camera for analytical purposes. Paper strips soaked with indoxylacetate were used for the determination of BChE activity, while the standard Ellman's assay was used as a reference measurement. In the smartphone-based assay, BChE converted indoxylacetate to indigo blue and coloration was photographed using the phone's integrated camera. A RGB color model was analyzed and color values for the individual color channels were determined. The assay was verified using plasma samples and samples containing pure BChE, and validated using Ellmans's assay. The smartphone assay was proved to be reliable and applicable for routine diagnoses where BChE serves as a marker (liver function tests; some poisonings, etc.). It can be concluded that the assay is expected to be of practical applicability because of the results' relevance.
Keywords: Mobile Applications; Enzyme Assays; Smartphone; diagnosis; RGB; butyrylcholinesterase; photography; myši inbrední BALB C; fotografování; CMYK; reprodukovatelnost výsledků; mobilní aplikace; acetylcholinesterase; Mice, Inbred BALB C; Reproducibility of Results; limita detekce; digital photography; chytrý telefon; Butyrylthiocholine; Animals; ženské pohlaví; Photography; Butyrylcholinesterase; zvířata; photometry; kolorimetrie; myši; Limit of Detection; butyrylthiocholin; mobile phone; butyrylcholinesterasa; Mice; enzymatické testy; Female; colorimetry; imagination; naked eye detection; Colorimetry